Kontestasi Hukum Islam dan Negara dalam Perda Bernuansa Syariah di Kota Tasikmalaya - Aziz, Abdul; Mutakin, Ali; Nugraha, Iqbal Subhan (STAINI Press, 2025)
The implementation of the Regional Regulation with sharia nuances in the city of Tasikmalaya often causes polemics related to the relationship between religious norms and the principle of the state of law that upholds diversity. This study aims to analyze the form, motive, and impact of the Sharia Nuanced Regional Regulation in Tasikmalaya City in the framework of the contestation between Islamic law and the state. The method used is qualitative with a socio-legal approach, through field studies and document analysis, as well as interviews with key legislative actors and religious organizations. The results of the study show that the Regional Regulation reflects more transactional political strategies between local elites and religious groups, rather than purely the normative aspirations of the community. Its application tends to be symbolic and does not have a significant impact on improving the quality of life of the community at large. The implications of these findings underscore the importance of evaluating local legislation to be in line with the principles of non-discrimination, substantive democracy, and the protection of the civil rights of all citizens without exception.